Sustain me with raisin-cakes : Pesikta deRav Kahana and the popularization of rabbinic Judaism - Anisfeld, Rachel A. (Supplements to the Journal for the Study of Judaism, 2009)
History and literature come together in a new way in this study of the midrashic collection Pesikta deRav Kahana. The book combines the findings of rabbinic historians and early Christianity scholars with a close reading of this midrashic text on its own and in relation to the tannaitic midrashim which preceded it. The rich picture that emerges suggests that PRK, in its new homiletical and aggadic stance, develops a religious language more appealing and accessible to the masses, an outreach language meant to win rabbinic popularity. Exploring issues of power and rhetoric, the book also places PRK's outreach language into the cultural context of the imperialism of Roman Christian homily.